Ultra-long-term human salt balance studies reveal interrelations between sodium, potassium, and chloride intake and excretion - Birukov, Anna; Rakova, Natalia; Lerchl, Kathrin; Engberink, Rik H. G. Olde; Johannes, Bernd; Wabel, Peter; Moissl, Ulrich; Rauh, Manfred; Luft, Friedrich C.; Titze, Jens (American Journal of Clinical Nutrition, 2016)
BACKGROUND: The intake of sodium, chloride, and potassium is considered important to healthy nutrition and cardiovascular disease risk. Estimating the intake of these electrolytes is difficult and usually predicated on urine collections, commonly for 24 h, which are considered the gold standard. We reported on data earlier for sodium but not for potassium or chloride. OBJECTIVE: We were able to test the value of 24-h urine collections in a unique, ultra-long-term balance study conducted during a simulated trip to Mars. DESIGN: Four healthy men were observed while ingesting 12 g salt/d, 9 g salt/d, and 6 g salt/d, while their potassium intake was maintained at 4 g/d for 105 d. Six healthy men were studied while ingesting 12 g salt/d, 9 g salt/d, and 6 g salt/d, with a re-exposure of 12 g/d, while their potassium intake was maintained at 4 g/d for 205 d. Food intake and other constituents were recorded every day for each subject. All urine output was collected daily. RESULTS: Long-term urine recovery rates for all 3 electrolytes were very high. Rather than the expected constant daily excretion related to daily intake, we observed remarkable daily variation in excretion, with a 7-d infradian rhythm at a relatively constant intake. We monitored 24-h aldosterone excretion in these studies and found that aldosterone appeared to be the regulator for all 3 electrolytes. We report Bland-Altman analyses on the value of urine collections to estimate intake. CONCLUSIONS: A single 24-h urine collection cannot predict sodium, potassium, or chloride intake; thus, multiple collections are necessary. This information is important when assessing electrolyte intake in individuals.
EVALuna2:33935